Kapabilitas LOTS dan HOTS Instrumen Penilaian Buatan Guru Sekolah Dasar Di Jakarta - Puji Hartini; Ernawati Ernawati; Hari Setiadi (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Assessment is a crucial step for determining whether or not a learning process has been successful. High-order thinking skills are a requirement for learning achievement in the twenty-first century. The goal of this project is to put quantitative evaluation instruments created by Jakarta elementary school teachers to the test. Methods: A mix method is used, which combines descriptive qualitative research with document analysis and quantitative research with instrument testing on reproductive system material, which is then examined using Anates. The participants in this study were eight Jakarta-based grade VI primary school teachers. Results: It demonstrates that teachers' capacity to construct evaluation instruments varies widely. Testing using Anates shows 15% of the questions compiled are valid and 85% invalid, 1 school with strong reliability and 7 other schools are less reliable. The difference shows that 42.5% are accepted and 57.5% are rejected. The level of difficulty showed that as many as 8.75% of the questions were in the very easy category, 18.75% easy, 51.25% moderate, 7.5% difficult and 13.75 very difficult. These results form the basis of the importance of the hierarchy of teacher understanding in depth, especially in relation to the preparation of HOTS-based assessment instruments because the quality of learning success is largely determined by the assessment instrument used. Conclusions: The LOTS and HOTS-based capability instruments made by the teacher at 8 East Dijakarta Elementary Schools have not been maximized and need development by these teachers.